Diabetes-related amputations in Germany: analysis of time trend from 2015 to 2022 and differences by area-level socioeconomic deprivation - Oktay Tuncer; Yong Du; Niels Michalski; Lukas Reitzle (Journal of Health Monitoring, 2024)
Background: Diabetes-related amputations reduce health-related quality of life and are an indicator of the quality of care of diabetes. Methods: Population-based age-standardized rates for diabetes-related cases of major and minor amputation were calculated and reported for the years 2015 – 2022 using the Diagnosis-related groups statistics. For 2022 these rates were also reported according to area-level socioeconomic deprivation. Results: Diabetes-related major amputations decreased from 6.8 to 5.2 per 100,000 residents in women and from 18.6 to 17.5 per 100,000 residents in men between 2015 and 2022. In 2021 and 2022, there was no further decrease in men compared to the previous year. Diabetes-related minor amputations decreased in women between 2015 and 2022, but increased in men. Amputation rates were higher in regions with high deprivation than in regions with low deprivation. Conclusions: Diabetes care should consider socioeconomic differences into account. The monitoring of the trends in amputations needs to be continued.